Academic Performance of Selected Grade 12 Humanities and Social Sciences Strand Students: As Influenced by Classroom Environment at Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The environment can significantly affect the action of every human. The environment can also give people a lesson on value things around them. Specifically, the environment of the teacher is important. The classroom’s physical environment affects the morale of the students and their learning. Including students in creating a positive physical environment can increase the feeling of classroom community and can give a student a sense of empowerment. The student can also feel calm in a good classroom environment. This study used the descriptive method. This study also used quantitative research that used a survey or questionnaire to gather information needed for this study. The best qualifiers are respondents who often get affected by academic performance. The study revealed that the group of 90 students for M/W/F scheduler answered that the physical aspect affects their academic performance. The average composite weighted mean for cleanliness was 3.56. The researchers concluded that the environment is important to the academic performance of Grade 12 Humanities and Social Sciences Strand students, especially in terms of cleanliness, having rusty chairs, and proper segregation; some students have solved and handled this kind of problem. Students prefer a clean classroom. Hence, the students must be reminded before having quizzes or examinations to prevent mental blocks. Students should have a comfortable arrangement inside the classroom to maintain their academic performance.
Keywords: academic performance, classroom environment